Efektivitas manajemen risiko dalam meningkatkan kinerja keuangan lembaga keuangan syariah - Fatkhunnaja, Achmad Iqbal (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the effectiveness of risk management in improving the financial performance of Islamic financial institutions. Risk management is proxied through the Capital Adequacy Ratio (CAR), Operating Costs to Operating Income (BOPO), and Non-Performing Loans (NPL), while financial performance is measured using Return on Assets (ROA). The research method used is a quantitative approach using secondary data in the form of Islamic financial institutions’ financial reports. Data analysis was conducted using multiple linear regression techniques to determine the influence of variables simultaneously and partially. The results show that risk management simultaneously has a significant effect on financial performance. Partially, BOPO has a negative and significant effect on ROA, while CAR and NPL have no significant effect. These findings indicate that operational efficiency is a major factor in improving the financial performance of Islamic financial institutions. Thus, the implementation of effective risk management, especially in controlling operational costs, is key to increasing profitability.